2019
DOI: 10.1186/s41983-019-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Do core stability exercises improve upper limb function in chronic stroke patients?

Abstract: Background: Upper limb paresis is a common problem in patients with stroke. Objectives: To determine the effect of core stability exercises on upper limb function and trunk balance in hemiparetic patients. Subjects: Thirty patients with hemiparesis, with age between 45 and 60 years, and with illness duration of more than 6 months. They were assigned into two equal groups, the control group, Group A: with 15 patients who received only conventional physical therapy program; the study group, Group B: with 15 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Figure 1 shows the flow details of the trials selected in the different phases. A total of 14 studies were identified for inclusion in the review, totaling 490 participants analyzed 8,27–39 . The characteristics of the studies included are shown on Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 shows the flow details of the trials selected in the different phases. A total of 14 studies were identified for inclusion in the review, totaling 490 participants analyzed 8,27–39 . The characteristics of the studies included are shown on Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included are shown on Table 1. Four studies were not included in the quantitative analysis because their outcome measures were not included in the at least three studies 30,34 or they did not provide raw data for the analysis 8,31 . They were all published between 2010 and 2019.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations